Meta-analysis in psychological research - Sánchez-Meca, Julio (Editorial Bonaventuriana, 2018)
Meta-analysis is a research methodology that aims to quantitatively integrate the results of a set of empirical studies about a given topic. With this purpose, effect-size indices are obtained from the individual studies and the characteristics of the studies are coded in order to examine their relationships with the effect sizes. Statistical analysis in meta-analysis requires the weighting of each effect estimate as a function of its precision, by assuming a fixed- or a randomeffects model. This paper outlines the steps required for carrying out the statistical analyses in a meta-analysis, the different statistical models that can be assumed, and the consequences of the assumptions in interpreting their results. The statistical analyses are illustrated with a real example.